Progress towards a holistic land and marine surface meteorological database and a call for additional contributions. (20th November 2020) - Noone, Simon; Atkinson, Chris; Berry, David I.; Dunn, Robert J. H.; Freeman, Eric; Perez Gonzalez, Irene; Kennedy, John J.; Kent, Elizabeth C.; Kettle, Anthony; McNeill, Shelley; Menne, Matthew; Stephens, Ag; et al.
Abstract: This paper outlines progress of the Copernicus Climate Change Service's (C3S) Global Land and Marine Observations Database service in securing data sources and introduces the data upload component. We present details of land and marine data holdings inventoried, highlighting priority needs in terms of periods, regions and Essential Climate Variables (ECVs) where additional data could bring most benefit. These holdings are being iteratively merged and integrated to best meet user needs and are served to the user via the Copernicus Climate Data Store (CDS). The secure Data Upload Server enables any data provider to share additional data and metadata with the service. We outline the process for registering as a data provider and how data sets are prioritized for integration. We encourage all data owners to share their data with the C3S service via our Data Upload Server. All unique and relevant data acquired or submitted will be also archived at the NOAA National Centers for Environmental Information World Data Center for Meteorology, Asheville, North Carolina, USA and used in their database curation efforts which are being jointly developed. Abstract : This paper outlines progress of the Copernicus Climate Change Service's (C3S) Global Land and Marine Observations Database service. We present details of land and marine data holdings inventoried, highlighting priority needs in terms of periods, regions and Essential Climate Variables (ECVs), and we introduce the data upload component so data providers can share their data. These holdings are being iteratively merged and integrated and served via the Copernicus Climate Data Store (CDS).